Phosphorus fractions in leaves - Suriyagoda, Lalith D. B.; Ryan, Megan H.; Gille, Clément E.; Dayrell, Roberta L. C.; Finnegan, Patrick M.; Ranathunge, Kosala; Nicol, Dion; Lambers, Hans (The New phytologist, 2023)
Summary Leaf phosphorus (P) comprises four major fractions: inorganic phosphate (Pi), nucleic acids, phospholipids, P‐containing metabolites and a residual fraction. In this review paper, we investigated whether allocation of P fractions varies among groups of terrestrial vascular plants, and is indicative of a species' strategy to use P efficiently. We found that as leaf total P concentration increases, the Pi fraction increases the most, without a plateau, while other fractions plateau. Variability of the concentrations of leaf P fractions is greatest among families > species(family) > regions > plant life forms. The percentage of total P allocated to nucleic acid‐P (20–35%) and lipid‐P (14–34%) varies less among families/species. High photosynthetic P‐use efficiency is associated with low concentrations of all P fractions, and preferential allocation of P to metabolite‐P and mesophyll cells. Sequential resorption of P from senescing leaves starts with Pi, followed by metabolite‐P, and then other organic P fractions. Allocation of P to leaf P fractions varies with season. Leaf phytate concentrations vary considerably among species, associated with variation in photosynthesis and defence. Plasticity of P allocation to its fractions is important for acclimation to low soil P availability, and species‐specific P allocation is needed for co‐occurrence with other species.